Cost-effectiveness of ribociclib for premenopausal or perimenopausal women with HR+/HER2− advanced breast cancer: a Brazilian public health care system perspective. (May 2022) - Rosa, Daniela Dornelles; Magliano, Carlos Alberto da Silva; Simon, Sergio D.; Amorim, Gilberto; Reinert, Tomás; Landeiro, Luciana; Gagliato, Débora de Melo; Exman, Pedro; Argolo, Daniel; Guilgen, Gisah; Mano, Max; Testa, Laura; et al.
Introduction: The MONALEESA-7 trial compared ribociclib plus endocrine therapy (ET) with placebo as first-line treatment of advanced luminal/HER2-negative breast cancer (ABC) in premenopausal and perimenopausal women (age <50 years) and showed significant benefits to progression-free survival and overall survival. This study aimed to compare the cost-effectiveness of ribociclib + ET versus ET alone in patients with ABC from the perspective of the Brazilian public national health system. Methods: We calculated the incremental cost-effectiveness ratio (ICER) using a Markov model with progression-free survival, post-progression survival, and death states. We expressed ICER as incremental costs per progression-free life-year (PFLY) and quality-adjusted life-year (QALY) gained in a 10-year time horizon. We used parametric survival distributions fit to MONALEESA-7 data to generate survival distributions for progression-free and post-progression survival. The largest British preference study in breast cancer served as the basis to estimate health-state utilities. We estimated direct costs (ABC treatment, follow-up, monitoring, and adverse events) using Brazilian-specific values from public sources. An expert consensus panel determined the resource patterns required. We applied annual discounts of 5% to costs and QALYs. Results: Ribociclib + ET resulted in an incremental gain of 1.03 PFLYs and 0.80 QALYs at a cost of 37, 319.31. The ICER of ribociclib + ET versus ET was 36, 379.41 per PFLY gained and 46, 590.79 per QALY gained. In deterministic sensitivity analysis, results were primarily affected by the annual discount rate, followed by the cost of ribociclib. In probabilistic sensitivity analysis, simulations agreed with the base-case. Conclusion: Ribociclib increased PFLYs and QALYs in patients with HR+/HER2− ABC when added to ET. Because Brazil does not have a formally defined cost-effectiveness threshold, other domains need to be considered for incorporation decisions, such as disease burden and humanistic impact on this young, economically active population. These findings may be useful in discussions for incorporation of ribociclib into the Brazilian public health system.